Answer:
6
Step-by-step explanation:
This quadratic needs to be in standard form.
[tex]f(x) = a {x}^{2} + bx + c[/tex]
[tex]8 {x}^{2} = - 7x + 6[/tex]
Subtract [tex]8 {x}^{2} [/tex] from both sides of the equation.
[tex]8 {x}^{2} - 8 {x}^{2} = - 8 {x}^{2} - 7x + 6 [/tex]
[tex] - 8 {x}^{2} - 7x + 6[/tex]
The constant is the value that stays "constant" or doesn't have a variable. In quadratics in standard form, the constant is the [tex]c[/tex] value.
[tex]a = - 8[/tex]
[tex]b = - 7[/tex]
[tex]c = 6[/tex]
Since the [tex]c[/tex] value is 6, the constant is equal to 6